2006
DOI: 10.1080/01926180600553878
|View full text |Cite
|
Sign up to set email alerts
|

Recognizing and Responding to Partner Violence: An Analog Study

Abstract: 1991) that investigated whether clinicians recognized and responded to indicators of intimate partner violence. In the current study participants included 112 mental health clinicians who read a clinical vignette, then responded to several open-ended questions, while still blind to the purpose of the study. Participants then answered several objective questions about how they respond when treating cases of intimate partner violence. Logistic regressions were conducted for recognition of and response to partner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Further, there is question as to how well MFTs address power and gender Contemporary Theories and Violence 35 differences, or if they miss crucial violence dynamics because of limited training in violence (Jory, 2004;Knudson-Martin & Mahoney, 2009). Despite the criticisms, there is reason to hope that MFTs are becoming more prepared to help individuals and couples identify, reduce, and eliminate violence (Dersch, Harris, & Rappleyea, 2006). Although there are many important issues relevant to MFTs and violence, this article briefly examines appropriate approaches to treatment and assessment for MFTs working with violence.…”
Section: Introductionmentioning
confidence: 97%
“…Further, there is question as to how well MFTs address power and gender Contemporary Theories and Violence 35 differences, or if they miss crucial violence dynamics because of limited training in violence (Jory, 2004;Knudson-Martin & Mahoney, 2009). Despite the criticisms, there is reason to hope that MFTs are becoming more prepared to help individuals and couples identify, reduce, and eliminate violence (Dersch, Harris, & Rappleyea, 2006). Although there are many important issues relevant to MFTs and violence, this article briefly examines appropriate approaches to treatment and assessment for MFTs working with violence.…”
Section: Introductionmentioning
confidence: 97%
“…Of the studies included, MHPs included MFTs, social workers, counselors, psychologists, IPV service providers, substance abuse counselors, welfare managers, social work students, and family and marriage therapy students. Five themes were identified including lack of preparation and inadequate training in DV (Dersch et al, 2006;Fedina et al, 2017;Karakurt et al, 2013;Kress et al, 2008;Murray et al, 2015;Raphael-Dudley et al, 2008;Schneider, 2018;Todahl et al, 2008), benefits of DV training (Forgey et al, 2013;Kulkarni et al, 2015;McCloskey & Grigsby, 2005;Payne et al, 2007;Saunders et al, 2006), need for collaboration between service providers (Capezza et al, 2014;Macy & Goodbourn, 2012;Macy et al, 2009), stigmatizing attitudes and behaviors toward survivors (Crowe & Murray, 2015), and the advocate-survivor connection (Bogat et al, 2013;Wood, 2017). These studies can be found in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…working with IPV clients and highlighted that therapists lacked training related to these cases, ultimately influencing the therapists' ability to effectively practice with these clients (Karakurt et al, 2013). An additional study revealed ongoing concerns about the adequacy of family therapy training (Dersch et al, 2006). Some MHPs may feel unprepared to address IPV confidently, thus intervening prematurely without a thorough assessment of the situation.…”
mentioning
confidence: 99%
“…Many clinicians already use multi-axial assessments that are sensitive to some of the prominent financial concerns commonly addressed in systemic therapies: job distress, relational distress, suicidal ideation, sexual distress, communication difficulty, domestic violence, and addiction. It appears, however, that clinicians do not generally attend to client behaviors unless they are imminently harmful to the client (e.g., suicidal or homicidal ideation) or immediately relevant to the presenting concern (e.g., relational hostility, communication difficulty, or sexual distress) (Dersch, Harris, & Rappleyea, 2006). In a recent survey of Financial Therapy Association (FTA) members, only 15% of the 70 members surveyed indicated that they used any formalized assessment procedures to determine the severity of financial distress (Asbedo, McCoy, & Archuleta, 2013).…”
Section: Assessment Of Financial Affairsmentioning
confidence: 99%
“…Therapists have been observed committing attribution errors in their assessment procedures (Rappleyea, Harris & Dersch, 2008). An attribution error occurs when a therapist does not assess for a problem not explicitly stated on an intake form because they perceive that a client does not fit a preconceived profile of a person who might be struggling with such a problem (e.g., violent behavior, addiction issues, and financial distress) (Dersch et. al, 2006;Rappleyea et.…”
Section: Assessment Of Financial Affairsmentioning
confidence: 99%